Troubling 'freedom': Silences in post-apartheid environmental education - Noel Gough (Environmental Association of Southern Africa, 1999)
The cultural history of South Africa in the transition from apartheid to democracy is a rich and complex story of the intricate inter-relations of education, (eco)politics, and social justice. As an Australian environmental education researcher working frequently in South Africa during 1998-99, I have welcomed the opportunity to explore these relationships in the light of South Africa's new 'freedom'. However, the freedom that has accompanied the constitutional abolition of apartheid implies a liberty beyond the world of legislative politics. South African educators have increasingly had the liberty to reject not only the determinisms of apartheid, but also to reject other social arrangements that supported its ideological machinery, such as patriarchy, sexism, ethnic nationalism, and class and language biases. Nevertheless, the literature of environmental education in South Africa remains for the most part silent on issues of race, class and gender. Thus, in this essay, I trouble the concept of 'freedom' in post apartheid environmental education by asking: what are South African environmental educators using their newly found freedom for?